Exploring the sustainability of farmers’ livelihood–land use systems from a coupled coordination perspective - Liu, Zhaoxu; Sun, Jinghua; Li, Yu; Wang, Hao; Zhang, Ziyu (Frontiers in Sustainable Food Systems, 2024)
This study explores the relationship between rural households' livelihood capital status and land use effects (LUEs) in Qufu City, Shandong Province, China. The analysis is based on data collected through a triangulation method, combining quantitative (questionnaire) and qualitative (interview) approaches. Using a coupling degree (CD) model and a coupling coordination degree (CCD) model within a human-land system framework, this study evaluates the coupling and coordination between rural households' livelihoods and land use as subsystems. It also examines the impact of LUE and CCD on rural households' livelihood strategies through Skinner's reinforcement theory.Results indicate variable CD and CCD across households with different livelihood strategies. In particular, the CD for the four household types ranged from 0.9 to 1, denoting a high-level coupling stage, with off-farm employment-oriented households registering the highest degree of 0.996. In CCD, professional households achieved a high degree of 0.761, whereas the others displayed a medium coupling coordination stage between 0.5 and 0.7. Professional households and balanced households showed superior LUE and CCD, with more than 50% of these households planning to maintain their original strategies. By contrast, households with off-farm employment-oriented or conventional strategies exhibited low LUE and CCD, with fewer than 50% of these households planning to retain their initial strategies. Professional agriculture-based livelihood strategies help improve the livelihood levels of farmers and promote the rational use of cultivated land resources, thereby making them particularly attractive to households engaged in agricultural production. This research contributes insights valuable for promoting the sustainable development of rural households' livelihoods and land use.